Amended Description of the Genes for Synthesis of Actinomyces naeslundii T14V Type 1 Fimbriae and Associated Adhesin - Chen, Ping (American Society for Microbiology, 2007)
The type 1 fimbriae of Actinomyces naeslundii T14V mediate adhesion of this gram-positive species to the tooth surface. The present findings show that the locus for type 1 fimbria production in this strain includes three genes, fimQ for a minor fimbrial subunit that appears to be an adhesin, fimP for the major structural subunit, and srtC1 for a type 1 fimbria-specific sortase involved in the assembly of these structures.